Mullite-silica scaffolds obtained by stereolithography and reaction sintering - E. Rosado; R. Moreno (Open Ceramics, 2023)
Mullite is a widely used refractory ceramic due to its good properties and high temperature stability. The necessity to obtain complex mullite architectures has encouraged the development of new AM techniques with improved resolution and surface finishing quality. In the present work, mullite-based scaffolds were obtained by stereolithography using a commercial silica resin and alumina nanoparticles following two routes: infiltration of printed porous silica parts with a colloidal alumina sol and printing of silica/alumina parts by developing a photocurable alumina resin that is mixed with the silica one. Post-processing of the obtained parts was carried out, including debinding and subsequent reaction sintering of the starting ceramic materials to give rise to mullite phase. All materials were characterised in terms of composition and microstructure, demonstrating that the second route results more effective to produce mullite structures in the final parts due to the higher alumina concentration and the larger reaction surface.